Diversity and habitat characteristics of macrozoobenthos in the mangrove forest of Lubuk Kertang Village, North Sumatra, Indonesia - MOHAMMAD BASYUNI; KRISTIAN GULTOM; ANNISA FITRI; IPANNA ENGGAR SUSETYA; RIDHA WATI; BEJO SLAMET; NURDIN SULISTIYONO; ERA YUSRIANI; THORSTEN BALKE; PETE BUNTING (Society for Indonesian Biodiversity, 2018)
Basyuni M, Gultom K, Fitri A, Susetya EA, Wati R, Slamet B, Sulistiyono N, Yusriani E, Balke T, Bunting P. 2018. Diversity and habitat characteristics of macrozoobenthos in the mangrove forest of Lubuk Kertang Village, North Sumatra, Indonesia. Biodiversitas 19: 311-317. Mangrove plays an important role in coastal ecosystems including ecological, social, and economic aspects. This study aimed to determine the diversity of macrozoobenthos and water quality based on diversity index (H’), similarity Index (E), and dominance index (D) in the mangrove of Lubuk Kertang Village North Sumatra, Indonesia. The samples of macrozoobenthos (biological parameter) and water quality (physical and chemical parameters) were collected from fifteen plots in three different stations. Macrozoobenthos were collected in 1 m × 1 m transect in the mangrove forest. The biota was taken by using a shovel, inserted into a plastic bag, and identified. Results showed that eight species of macrozoobenthos were found and classified into three classes of Gastropod, Bivalvia, and Malacostraca. The highest diversity index (H?) of macrozoobenthos was found at Station II (2.39), the highest evenness index (E) was located at Station I (0.54), and the highest dominance index (D) was found at Station II (0.34). Principal component analysis (PCA) was used to determine the habitat characteristics of macrozoobenthos. PCA confirmed that station III was a habitat with suitable characteristics for the life of macrozoobenthos indicating the negative axis. The present study suggested four parameters namely salinity, clay temperature, and dissolved oxygen that should be preserved to support the survival of macrozoobenthos in the mangrove forests.